Childcare Providers' Use of Practices to Promote Young Children's Social–Emotional Competence. Issue 2 (April 2017) - Steed, Elizabeth A.; Roach, Andrew T.
Abstract : Findings are presented regarding childcare providers' use of evidence-based strategies to promote preschoolers' social–emotional competence in 38 urban childcare classrooms. Descriptive results from classroom observations and childcare teachers' interviews indicated that in the absence of training, childcare teaching staff implemented few of these strategies. Teachers also reported a lack of infrastructure elements such as professional development, a leadership team, data-based tools for decision making, and monetary resources that are associated with the adoption and sustained use of strategies. Findings are described and recommendations are presented to support implementation of practices associated with young children's social–emotional competence in childcare settings.